Desafiando las estructuras jurídicas de despojo desde lo local - Gómez Rojas, Ana Carolina (Pontificia Universidad Católica del Perú, 2024)
Latin America is framed within a neoliberal rationality that favors the installation of legal structures of dispossession (LSD) (Hernández, 2019). However, local communities resist and counterattack in diverse ways, including legal and political. A space for observing these dynamics is the socio-environmental conflict derived from the La Colosa gold mining project in Colombia, since, through the use of mechanisms such as popular consultation, new institutional agreements have been reached challenging the traditional distribution of power over the territory. The central argument is that the case of resistance to megaprojects through legal mechanisms helps to observe the processes of institutionalized resistance that transform legal structures to give way to a different relationship between nature-society. Methodologically, the argument is based on participant and participatory observation, semi-structured interviews, documentary, and journalistic review between 2013 and 2022, and review of judicial documents from a documentary ethnography perspective (Muzzopappa Villalta, 2013). Despite the asymmetry of power in which socio-environmental disputes develop, the results show that there are multiple interactions challenging the hegemonic power from the local level, forcing it to a permanent territorial reflexivity. In addition, it is based off the responses from organized communities, public authorities, and corporations that the strategies for the following stages of the conflict arise. This implies that any conflict is not beforehand resolved.

América Latina se enmarca en una racionalidad neoliberal que favorece la instalación de estructuras jurídicas de despojo (EJD) (Hernández, 2019). Sin embargo, las comunidades locales resisten y contraatacan de distintas formas, entre ellas, la jurídico-política. Un espacio de observación de estas dinámicas es el conflicto socioambiental derivado del proyecto aurífero La Colosa en Colombia, ya que, a través el uso de mecanismos como la consulta popular, las comunidades en Cajamarca han logrado nuevos acuerdos institucionales que desafían el reparto tradicional de poder sobre el territorio. El argumento central es que la resistencia a megaproyectos a través de mecanismos jurídicos dinamiza las estructuras legales de los gobiernos nacionales para dar paso a una relación distinta entre naturaleza-sociedad, y ello se logra a través de distintas transacciones territoriales, es decir, de negociaciones sobre lo que se había presentado inicialmente como incompatible y no negociable (Melé, 2014). Metodológicamente, el argumento se sustenta en la realización de observación participante y participativa, entrevistas semiestructuradas, revisión documental y periodística entre 2013 y 2022, y revisión de documentos judiciales desde una perspectiva de etnografía documental (Muzzopappa Villalta, 2013). Los resultados apuntan a que, a pesar de la asimetría de poder en la que se desarrollan las disputas socioambientales, desde lo local hay múltiples interacciones que desafían al poder hegemónico y lo obligan a una reflexividad territorial permanente. Además, es a partir de las respuestas entre comunidad organizada, autoridades públicas y empresa que surgen las estrategias para las siguientes etapas del conflicto. Esto implica que ningún conflicto está resuelto de antemano.
Challenging the Legal Structures of Dispossession from the Local
Keywords: Socio-environmental conflict; Legal structures of dispossession; Cajamarca; La Colosa; Territoriality; Control territorial; Conflicto socioambiental; Estructuras jurídicas del despojo; Cajamarca; La Colosa; https://purl.org/pe-repo/ocde/ford#5.04.00